Analysis of Purity and Concentration Escherichia coli DNA by Boiling Method Isolation with Addition of Proteinase-K and RNase - Lesiani, Bunga Rossa; Abror, Yogi Khoirul; Merdekawati, Fusvita; Djuminar, Ai (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2023)
Escherichia coli is a leading cause of Urinary Tract Infections (UTIs) in Indonesia, with approximately 180,000 cases reported annually. The more cases of UTIs, the more PCR diagnosis is needed with an accurate, fast, simple, and economical DNA isolation method. However, currently, there is no DNA purification stage from protein and RNA contaminants in the boiling DNA isolation method. This study aimed to investigate the impact of incorporating Proteinase-K and RNase into the boiling DNA isolation method on the purity and concentration of E. coli’s DNA during isolation. The boiling method involved heating to 95°C – 100°C bring to cell lysis and release of cellular components, including DNA. Urine samples were artificially contaminated with E. coli at different McFarland standards (0.25, 0.5, and 1). The boiling DNA isolation method was then performed and then analyzed for purity and concentration using a NanoDrop spectrophotometer. This study demonstrated a positive correlation between Proteinase-K and RNase concentrations used in the boiling DNA isolation method and the subsequent increase in DNA purity and concentration. An increase in DNA purity and concentration was obtained even though it was not statistically significant compared to that without Proteinase-K and RNase addition, with p-values of 0.245 for DNA purity and 0.353 for DNA concentration. Further research is recommended with higher Proteinase-K and RNase concentrations in the boiling DNA isolation method to achieve improved purity and concentration of E. coli DNA. Such enhancements could improve PCR amplification and help diagnose E. coli-related UTIs.